Effect of Acid Pickling on Microstructure and Surface Roughness of 316L Stainless Steel - Rahil Izzati, Mohd Asri; Wan Sharuzi, Wan Harun; Asmara, Y. P. (Universiti Malaysia Pahang, 2016)
Hydrofluoric and Nitric acids solution with additional of water were tested as pickling solutions for 316L stainless steel before application of hydroxyapatite coatings. Pickling was explored at room temperature for 5-10-15 min. The microstructure of surface layer, surface roughness and microhardness of 316L stainless steel treated by acid pickling were investigated in this study. The microstructure and surface morphology were examined by an optical microscope (OM) and scanning electron microscope (SEM), while surface roughness was measured by using perthometer (Mahr). The experimental result showed that increment of surface roughness when longer exposed to the acids solution. Microhardness values were higher than annealed sample. It is expected that surface treated 316L stainless steel strongly adhere to the coating after applying acid pickling treatment.